Case Management of Counseling Guidance for Inmates Experience Stress During Early Coaching - Equatora, Muhammad Ali; Rachim, Hadiyanto Abdul; Nulhakim, Soni Akhmad; Raharjo, Santoso Tri (Universitas Muhammadiyah Yogyakarta, 2024)
The phenomenon of stress in prisoners is currently an urgency for various researchers. This stress occurs because it is experienced due to changes in the atmosphere of the general public, but entering a criminal facility makes them feel uncomfortable, starting from mental pressure, anxiety, anti-social behavior, and even suicide due to stress. Therefore, there is a need for case management so that inmates can face situations of stress and fear when undergoing initial formation in state detention centers. This study used a qualitative research method with a case study research design, employing observation, study documentation, and interviews for data collection. There were 6 informants, 1 of whom was a prisoner, along with 1 guard officer, 1 registration officer, and 3 inmates. This research emphasizes interactive data analysis and qualitative confirmation of source triangulation results. The object of research lies in how prisoners can undergo an excellent initial coaching period to manage stressful situations and fears. The results of this research indicate that correctional guardians have a role in providing counseling guidance on the stress of inmates during initial training at the Painan Detention Center, where the stress levels of inmates are very high. The effective counseling guidance methods or techniques used include a religious approach to reduce stress on inmates during the initial training period. This action seeks to reduce stress levels and provide assistance to prisoners. This research presents a novelty that lies in the experience of stress management during the initial guidance of inmates.